2021
DOI: 10.1172/jci143078
|View full text |Cite
|
Sign up to set email alerts
|

C2orf69 mutations disrupt mitochondrial function and cause a multisystem human disorder with recurring autoinflammation

Abstract: Background: Deciphering the function of the many genes previously classified as uncharacterized "open reading frame" (orf) completes our understanding of cell function and its pathophysiology. Methods: Whole-exome sequencing, yeast 2-hybrid and transcriptome analyses together with molecular characterization are used here to uncover the function of the C2orf69 gene. Results: We identified loss-of-function mutations in the uncharacterized C2orf69 gene in eight individuals with brain abnormalities involving hypom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(17 reference statements)
2
12
0
Order By: Relevance
“…Notably, C2orf69-Brain Caudate basal ganglia gene-trait pair was the only one observed overlapping gene-tissue pair between smoking status and HF. C2orf69 is an evolutionarily conserved gene whose function needs to be further clarified, but recent studies have shown its association with a fatal autoinflammatory syndrome that disrupts the development/homeostasis of the immune and central nervous systems (102,103), which may contribute to the link between smoking and HF.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, C2orf69-Brain Caudate basal ganglia gene-trait pair was the only one observed overlapping gene-tissue pair between smoking status and HF. C2orf69 is an evolutionarily conserved gene whose function needs to be further clarified, but recent studies have shown its association with a fatal autoinflammatory syndrome that disrupts the development/homeostasis of the immune and central nervous systems (102,103), which may contribute to the link between smoking and HF.…”
Section: Discussionmentioning
confidence: 99%
“…IKZF1 GOF [52]) (Table 4; Supplementary Table 1) • neutropenia CXCR2 [53,54] (Table 5, Supplementary Table 1) • innate immune defects resulting in susceptibility to mycobacterial/bacterial (TBX21 [55,56], IFNG [57], TLR8 [58,59]), viral (NOS2 [60], SNORA31 [61], ATG4A, MAP1LC3B2 [62], ZNFX1 [63][64][65], TLR7 [66][67][68]), and/or fungal infections (MAPK8 [69]) (Table 6; Supplementary Table 1); • Autoimmune/autoinflammatory disorders (TMEM173 [70], LSM11, RNU7-1 [71], CDC42 [72][73][74][75][76][77][78], STAT2 [79,80], ATAD3A [81], AR TBK1 [82], C2orf69 [83,84], RIPK1 [85,86], NCKAP1L [87][88][89], SYK [90], HCK1 [91], IKBKG…”
Section: Novel Inborn Errors Of Immunitymentioning
confidence: 99%
“…• The small nucleolar RNA SNORA31 plays a critical role in CNS-intrinsic immunity against HSV-2 infection, likely via production of type 1 IFN, yet the exact mechanism remains unknown [61]. • The hitherto uncharacterized protein-coding gene C2orf69 has a multitude of roles across numerous biological systems, including regulating autoinflammation [83,84].…”
Section: Iei Define Specific Roles For Known Genes and Reveal Immune-...mentioning
confidence: 99%
See 1 more Smart Citation
“…We also noted pronounced upregulation of C2orf69, a regulator of mitochondrial function (Lausberg et al, 2021; Wong et al, 2021), in both SCZ (LFC = 2.02, FDR-adj. P: = 0.004) and BP synapses (LFC = 2.06; FDR-adj.…”
Section: Resultsmentioning
confidence: 78%